High-thermal-conductivity and high-heat-resistance copper-clad plate and preparation method thereof
By introducing epoxy groups and branched biphenyl modification on the surface of aluminum nitride, and optimizing the resin matrix with anhydride curing agent, the problem of insufficient thermal conductivity and heat resistance of copper clad sheet materials in high temperature environments is solved, and the material's high thermal conductivity, high heat resistance and good mechanical properties are achieved. It is suitable for high power density electronic device packaging.
Patent Information
- Application Number
- CN202510673281.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-05-23
- Publication Date
- 2025-07-18
AI Technical Summary
The existing copper clad materials have insufficient thermal conductivity and heat resistance under high power density and high temperature environments. The interface bonding force between the filler and the resin matrix is weak, and the filler is prone to agglomeration, resulting in deterioration of the material performance. The molecular structure design of the resin matrix cannot effectively improve the long-term stability of the material.
By introducing epoxy groups on the surface of aluminum nitride and synergistic with branched biphenyls, a continuous thermal conductivity network is constructed to form a multi-dentate coordination effect, and a dense crosslinking network is formed with an acid anhydride curing agent to optimize the molecular structure of the resin matrix to enhance interface binding force and heat resistance.
The thermal conductivity, heat resistance and mechanical properties of copper clad plate are significantly improved, and are suitable for electronic device packaging in high power density and high temperature environments. The performance stability and uniformity of the material at high temperatures are improved.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of copper clad laminates, and particularly to a high thermal conductivity and high heat resistance copper clad laminate and a preparation method thereof. Background Art
[0002] With the development of electronic devices, especially in the fields of high power density and high frequency, the performance requirements for electronic packaging materials are increasing day by day. As one of the core materials of electronic devices, the performance of copper clad laminates directly determines the thermal conductivity, mechanical strength, and long-term stability of circuit boards. However, the traditional copper clad laminate materials have low thermal conductivity and heat resistance, making it difficult to meet the requirements of modern electronic devices for high thermal management capabilities. To improve the thermal conductivity of copper clad laminates, researchers usually add high thermal conductivity fillers (such as aluminum nitride, alumina, or carbon-based materials) to the resin matrix to construct a thermal conduction path. However, the surface chemical inertness of the fillers results in weak interfacial bonding force between the fillers and the resin matrix, and the fillers are prone to agglomeration in the matrix, leading to a decrease in thermal conductivity and deterioration of the mechanical properties of the material. In addition, the presence of interfacial defects between the fillers and the matrix will also accelerate the performance decay of the material under high temperature conditions and reduce its long-term use reliability.
[0003] In recent years, the surface modification technology of functionalized fillers has gradually attracted attention. By introducing active groups on the surface of the fillers, the chemical bonding force between the fillers and the resin matrix can be enhanced, thereby improving the interfacial properties. However, conventional filler modification methods usually simply introduce a single active group, such as amino, hydroxyl, or epoxy groups, etc. This type of single-point bonding method is difficult to form a stable interfacial network, resulting in limited bonding force between the fillers and the matrix. At the same time, fillers with a single active group are prone to agglomeration at high filling amounts, further reducing the thermal conductivity and mechanical properties of the material. Therefore, how to comprehensively improve the interfacial properties through the surface functionalization design of fillers has become a key technical problem in improving the performance of thermal conductive composites.
[0004] On the other hand, the molecular structure design of the resin matrix also plays an important role in the heat resistance and mechanical properties of the material. Traditional epoxy resin matrices mostly use amine curing agents. Although the cross-linked network formed after curing can provide certain mechanical strength, due to the poor thermal stability of the ether bond structure, it is prone to decomposition or chain segment movement under high temperature conditions, resulting in rapid decay of the material properties. In addition, the rapid reaction characteristics of amine curing agents may lead to uneven distribution of fillers during the curing process, further increasing interfacial defects.
[0005] In summary, the existing technologies still face many challenges in improving the thermal conductivity, heat resistance, and mechanical properties of copper clad laminate materials: insufficient interfacial bonding force between the filler and the matrix leads to low thermal conductivity, filler agglomeration reduces the material properties, the choice of curing agent system affects the long-term stability of the material, and the optimized design of the resin matrix molecular structure has not been effectively combined with the surface modification technology of functional fillers. Summary of the Invention
[0006] In view of this, the purpose of the present invention is to provide a high thermal conductivity and high heat resistance copper clad laminate and its preparation method, so as to provide a copper clad laminate material with high thermal conductivity, high heat resistance, and good mechanical properties to meet the application requirements of electronic devices in high power density and high temperature environments.
[0007] Based on the above purpose, the present invention provides a high thermal conductivity and high heat resistance copper clad laminate, with a prepreg as the core layer, and electrolytic copper foils covered on both sides; the prepreg is obtained by impregnating a pretreated substrate into a resin adhesive solution and pre-curing.
[0008] Preferably, the pretreated substrate is obtained by plasma treatment of a glass fiber cloth; Preferably, the thickness of the electrolytic copper foil is 15 - 20 μm, and the roughness Rz is 2.5 - 3.5 μm.
[0009] Preferably, the pre-curing temperature is 145 - 155 °C, and the time is 6 - 10 min.
[0010] Preferably, the resin content after impregnating the pretreated substrate into the resin adhesive solution is 40% - 45%.
[0011] Preferably, the thickness of the glass fiber cloth is 0.4 - 0.6 mm.
[0012] Furthermore, the preparation steps of the resin adhesive solution are as follows: (1) Add 1,3,5-tris(4-aminophenyl)benzene and biphenyl-4-carbonyl chloride to tetrahydrofuran, cool down to 0 - 5 °C, add triethylamine, stir for 5 - 15 min, then heat up to 30 - 40 °C, stir and react for 15 - 25 h, and purify to obtain branched biphenyl; (2) Add aluminum nitride to an ethanol / deionized water mixed solution, ultrasonicate for 10 - 30 min, then add silane coupling agent KH-560, heat up to 50 - 60 °C, stir and react for 5 - 7 h, and purify to obtain epoxidized aluminum nitride; (3) Add epoxidized aluminum nitride and branched biphenyl to a methanol / deionized water mixed solution, adjust the pH to 8.1 - 8.6 with sodium hydroxide, heat up to 80 - 90 °C, reflux and stir for 20 - 28 h, and purify to obtain branched biphenyl modified aluminum nitride; (4) Mix bisphenol A epoxy resin, methyl nadic anhydride curing agent, and branched biphenyl modified aluminum nitride, heat up to 75 - 85 °C and stir for 1 - 2 h, cool down to room temperature, then add acetone and stir for 15 - 25 min to obtain a resin adhesive solution.
[0013] Preferably, in the step (1), the weight ratio of 1,3,5 - tris(4 - aminophenyl)benzene, biphenyl - 4 - carbonyl chloride, tetrahydrofuran, and triethylamine is 3.5:8.2 - 9.2:15 - 25:3 - 3.5.
[0014] Preferably, in the step (2), the particle size D50 of aluminum nitride is 0.5 - 1 μm.
[0015] Preferably, in the step (2), the weight ratio of aluminum nitride, ethanol / deionized water mixture, and silane coupling agent KH - 560 is 20 - 30:200 - 300:0.2 - 1.
[0016] Preferably, in the step (2), the volume ratio of ethanol to deionized water in the ethanol / deionized water mixture is 1:3.
[0017] Preferably, in the step (3), the weight ratio of epoxy - modified aluminum nitride, branched biphenyl, and methanol / deionized water mixture is 20 - 30:1.5 - 3.5:200 - 300.
[0018] Preferably, in the step (3), the volume ratio of methanol to deionized water in the methanol / deionized water mixture is 1:4.
[0019] Preferably, in the step (4), the weight ratio of bisphenol A epoxy resin, methyl nadic anhydride curing agent, branched biphenyl modified aluminum nitride, and acetone is 80 - 120:50 - 80:20 - 30:65 - 95.
[0020] Preferably, the model of the bisphenol A epoxy resin in the step (4) is E - 51.
[0021] Furthermore, the present invention also provides a preparation method of a high - thermal - conductivity and high - heat - resistance copper - clad laminate, comprising the following steps: S1: Take a glass fiber cloth, dry it at 110 - 130 °C for 1.5 - 2.5 h, then place it in a plasma cleaner and treat it with argon plasma, with a power of 250 - 350 W and a treatment time of 3 - 8 min to obtain a pretreated substrate; S2: Immerse the pretreated substrate in the resin adhesive solution and pre - cure it to obtain a prepreg; S3: Take the prepreg as the core layer, cover both sides with electrolytic copper foil, and form it using a vacuum hot press under the following conditions: The first stage: Heat up to 100 - 120°C at a rate of 2 - 4°C / min, maintain a pressure of 4 - 6 MPa, and keep the temperature and pressure for 20 - 40 min. The second stage: Continue to heat up to 170 - 190°C at a rate of 2 - 4°C / min, increase the pressure to 8 - 12 MPa, and keep the temperature and pressure for 70 - 110 min. The third stage: Cool down to 55 - 65°C at a rate of 0.5 - 3°C / min and then release the pressure to obtain a laminate. S4: Under nitrogen protection, post-cure the laminate at 215 - 225°C for 1.5 - 2.5 h, place it at room temperature for 36 - 50 h, and then cut it to obtain a high thermal conductivity and high heat resistance copper clad laminate.
[0022] Advantages of the present invention: By introducing epoxy groups on the surface of the filler and synergistically modifying it with branched biphenyl, the interfacial bonding strength between the filler and the resin matrix is significantly enhanced. The three-dimensional topological structure of branched biphenyl forms a multi-tooth coordination effect on the surface of the filler, effectively constructing a continuous thermal conduction network. At the same time, its rigid aromatic ring skeleton enhances the rigidity and stability of the matrix molecular chain. In addition, the chemical bond formed by the reaction of the epoxy group with the amino group of branched biphenyl further improves the interfacial strength and reduces the performance attenuation under high-temperature environments.
[0023] By introducing an anhydride curing agent, the present invention forms a denser cross-linked network structure. The thermal stability of its ester bond is better than the ether bond structure of traditional amine curing agents, significantly improving the heat resistance and long-term use stability of the material. At the same time, the slow characteristic of the anhydride curing reaction helps the uniform distribution of the filler in the matrix, reducing interfacial defects and further improving the thermal conductivity and mechanical properties of the material.
[0024] The present invention also constructs a dual interfacial enhancement mechanism of "chemical anchoring - physical interlocking" by optimizing the molecular structure design of the resin matrix and utilizing the chemical reactions between the multi-active sites of branched biphenyl and the filler and the matrix. The auxiliary physical cross-linking points formed by the π-π interaction between the biphenyl units of branched biphenyl further enhance the interfacial strength. At the same time, its steric hindrance effect effectively prevents the sedimentation and agglomeration of the filler, ensuring the uniformity and stability of the material.
[0025] In summary, through the synergistic effect of the functionalization design of the filler surface and the optimization of the matrix molecular structure, the present invention realizes a comprehensive improvement in thermal conductivity, heat resistance, and mechanical properties. This material exhibits excellent performance under high power density and high-temperature environments and has broad application prospects. Specific embodiments
[0026] To make the objectives, technical solutions, and advantages of the present invention clearer and more understandable, the following further elaborates on the present invention in detail with specific embodiments. Example 1:
[0027] (1) Add 3.5 g of 1,3,5-tris(4-aminophenyl)benzene and 8.2 g of 4-biphenylcarbonyl chloride to 15 g of tetrahydrofuran. Cool the temperature to 0 °C, add 3 g of triethylamine, stir for 5 min, then raise the temperature to 30 °C and stir for 15 h. Cool to room temperature, pour into water, collect the precipitate, dry in vacuum, and then recrystallize with a chloroform / tetrahydrofuran mixed solution (volume ratio 4:1), and dry in vacuum again to obtain branched biphenyl. (2) Add 20 g of aluminum nitride (particle size D50: 0.8 μm) to 200 g of an ethanol / deionized water mixed solution (volume ratio 1:3), ultrasonicate for 10 min, then add 0.2 g of silane coupling agent KH-560, raise the temperature to 50 °C, stir and react for 5 h, centrifuge, wash, and dry in vacuum to obtain epoxidized aluminum nitride. (3) Add 20 g of epoxidized aluminum nitride and 1.5 g of branched biphenyl to 200 g of a methanol / deionized water mixed solution (volume ratio 1:4), adjust the pH to 8.1 with sodium hydroxide, raise the temperature to 80 °C, reflux and stir for 20 h, cool to room temperature, centrifuge, wash 3 times with deionized water and methanol respectively, and dry in vacuum to obtain branched biphenyl-modified aluminum nitride. (4) Mix 80 g of bisphenol A epoxy resin (model: E-51), 50 g of methyl nadic anhydride curing agent and 20 g of branched biphenyl-modified aluminum nitride, raise the temperature to 75 °C and stir for 1 h, cool to room temperature, then add 65 g of acetone solvent and stir for 15 min to obtain a resin adhesive solution. (5) Take a glass fiber cloth with a thickness of 0.5 mm (model: 2116), dry it at 110 °C for 1.5 h to remove surface adsorbed moisture, then place it in a plasma cleaner and treat it with argon plasma at a power of 250 W for 3 min to obtain a pretreated substrate. (6) Immerse the pretreated substrate in the resin adhesive solution, control the resin content to 40%, and pre-cure at 145 °C for 6 min to obtain a semi-cured sheet. (7) Take 2 semi-cured sheets as the core layer and cover both sides with 18 μm electrolytic copper foil (roughness Rz = 3 μm). Use a vacuum hot press to form under the following conditions: First stage: Heat up to 100 °C at a rate of 2 °C / min, maintain a pressure of 4 MPa, keep the temperature and pressure for 20 min. Second stage: Continue to heat up to 170 °C at a rate of 2 °C / min, increase the pressure to 8 MPa, keep the temperature and pressure for 70 min. Third stage: Cool down to 55 °C at a rate of 0.5 °C / min and then release the pressure to obtain a laminate. (8) Under nitrogen protection, post-cure the laminate at 215 °C for 1.5 h, place it at room temperature for 36 h, and then cut to obtain a high thermal conductivity and high heat resistance copper clad laminate. Example 2:
[0028] (1) Add 3.5 g of 1,3,5-tris(4-aminophenyl)benzene and 8.7 g of 4-biphenylcarbonyl chloride to 20 g of tetrahydrofuran. Cool the temperature to 0 °C, add 3.2 g of triethylamine, stir for 10 min, then raise the temperature to 35 °C and stir for 20 h. Cool to room temperature, pour into water, collect the precipitate, dry it under vacuum, and then recrystallize it with a chloroform / tetrahydrofuran mixed solution (volume ratio 4:1), and dry it under vacuum again to obtain branched biphenyl; (2) Add 25 g of aluminum nitride (particle size D50: 0.8 μm) to 250 g of an ethanol / deionized water mixed solution (volume ratio 1:3), ultrasonicate for 20 min, then add 0.5 g of silane coupling agent KH-560, raise the temperature to 55 °C, stir and react for 6 h, centrifuge, wash, and dry under vacuum to obtain epoxidized aluminum nitride; (3) Add 25 g of epoxidized aluminum nitride and 2.5 g of branched biphenyl to 250 g of a methanol / deionized water mixed solution (volume ratio 1:4), adjust the pH to 8.5 with sodium hydroxide, raise the temperature to 85 °C, reflux and stir for 24 h, cool to room temperature, centrifuge, wash 3 times with deionized water and methanol respectively, and dry under vacuum to obtain branched biphenyl-modified aluminum nitride; (4) Mix 100 g of bisphenol A epoxy resin (model: E-51), 65 g of methyl nadic anhydride curing agent and 25 g of branched biphenyl-modified aluminum nitride, raise the temperature to 80 °C and stir for 1.5 h, cool to room temperature, then add 80 g of acetone solvent and stir for 20 min to obtain a resin adhesive solution; (5) Take a glass fiber cloth with a thickness of 0.5 mm (model: 2116), dry it at 120 °C for 2 h to remove surface adsorbed moisture, then place it in a plasma cleaner and treat it with argon plasma, with a power of 300 W and a treatment time of 5 min to obtain a pretreated substrate; (6) Immerse the pretreated substrate in the resin adhesive solution, control the resin content to 42%, and pre-cure it at 150 °C for 8 min to obtain a semi-cured sheet; (7) Take 2 semi-cured sheets as the core layer, and cover both sides with 18 μm electrolytic copper foil (roughness Rz = 3 μm). Use a vacuum hot press to form under the following conditions: The first stage: heat up to 110 °C at a rate of 3 °C / min, maintain a pressure of 5 MPa, keep the temperature and pressure for 30 min, the second stage: continue to heat up to 180 °C at a rate of 3 °C / min, increase the pressure to 10 MPa, keep the temperature and pressure for 90 min, the third stage: cool down to 60 °C at a rate of 1.5 °C / min and then release the pressure to obtain a laminate; (8) Under nitrogen protection, post-cure the laminate at 220 °C for 2 h, place it at room temperature for 48 h, and then cut it to obtain a high thermal conductivity and high heat resistance copper clad laminate. Example 3:
[0029] (1) Add 3.5 g of 1,3,5-tris(4-aminophenyl)benzene and 9.2 g of 4-biphenylcarbonyl chloride to 25 g of tetrahydrofuran. Cool the temperature to 5 °C, add 3.5 g of triethylamine, stir for 15 min, then raise the temperature to 40 °C and stir for 25 h. Cool to room temperature, pour into water, collect the precipitate, dry it under vacuum, and then recrystallize it with a chloroform / tetrahydrofuran mixed solution (volume ratio 4:1), and dry it under vacuum again to obtain branched biphenyl; (2) Add 30 g of aluminum nitride (particle size D50: 0.8 μm) to 300 g of an ethanol / deionized water mixed solution (volume ratio 1:3), ultrasonicate for 30 min, then add 1 g of silane coupling agent KH-560, raise the temperature to 60 °C, stir and react for 7 h, centrifuge, wash, and dry under vacuum to obtain epoxidized aluminum nitride; (3) Add 30 g of epoxidized aluminum nitride and 3.5 g of branched biphenyl to 300 g of a methanol / deionized water mixed solution (volume ratio 1:4), adjust the pH to 8.6 with sodium hydroxide, raise the temperature to 90 °C, reflux and stir for 28 h, cool to room temperature, centrifuge, wash 3 times with deionized water and methanol respectively, and dry under vacuum to obtain branched biphenyl modified aluminum nitride; (4) Mix 120 g of bisphenol A epoxy resin (model: E-51), 80 g of methyl nadic anhydride curing agent and 30 g of branched biphenyl modified aluminum nitride, raise the temperature to 85 °C and stir for 2 h, cool to room temperature, then add 95 g of acetone solvent and stir for 25 min to obtain a resin adhesive solution; (5) Take a glass fiber cloth with a thickness of 0.5 mm (model: 2116), dry it at 130 °C for 2.5 h to remove surface adsorbed moisture, then place it in a plasma cleaner and treat it with argon plasma at a power of 350 W for 8 min to obtain a pretreated substrate; (6) Immerse the pretreated substrate in the resin adhesive solution, control the resin content to 45%, and pre-cure it at 155 °C for 10 min to obtain a semi-cured sheet; (7) Take 2 semi-cured sheets as the core layer and cover both sides with 18 μm electrolytic copper foil (roughness Rz = 3 μm). Use a vacuum hot press to form under the following conditions: The first stage: heat up to 120 °C at a rate of 4 °C / min, maintain a pressure of 6 MPa, keep the temperature and pressure for 40 min, the second stage: continue to heat up to 190 °C at a rate of 4 °C / min, increase the pressure to 12 MPa, keep the temperature and pressure for 110 min, the third stage: cool down to 65 °C at a rate of 3 °C / min and then release the pressure to obtain a laminate; (8) Under nitrogen protection, post-cure the laminate at 225 °C for 2.5 h, place it at room temperature for 50 h, and then cut it to obtain a high thermal conductivity and high heat resistance copper clad laminate.
[0030] Comparative Example 1: The difference between Comparative Example 1 and Example 2 lies in that: the branched biphenyl in step (3) is replaced by 1,3,5-tris(4-aminophenyl)benzene; Comparative Example 2: The difference between Comparative Example 2 and Example 2 lies in that: the aluminum nitride epoxidized nitride in step (3) is replaced by aluminum nitride; Comparative Example 3: The difference between Comparative Example 3 and Example 2 lies in that: the branched biphenyl in step (3) is replaced by 4-aminobiphenyl; Comparative Example 4: The difference between Comparative Example 4 and Example 2 lies in that: the branched biphenyl modified aluminum nitride in step (4) is replaced by aluminum nitride; Comparative Example 5: The difference between Comparative Example 5 and Example 2 lies in that: the methyl nadic anhydride curing agent in step (4) is replaced by triethylenetetramine; Performance test: Thermal conductivity test: According to GB / T 3399-2022, the test is carried out by using a laser flash method thermal conductivity meter. The copper clad laminates prepared in the examples and comparative examples are cut into standard specimens. When testing, the heat source temperature is set at 100 °C and the cold source temperature is set at 20 °C. The arithmetic mean of three valid measurement values is recorded as the final result. The results are shown in Table 1.
[0031] Peel strength test: According to GB / T 4722-2017, a 180° peel test is carried out by using a universal material testing machine. The copper clad laminates prepared in the examples and comparative examples are cut into standard specimens. The peeling length at the end of the copper foil is reserved at 20 mm, and the test speed is set at 50 mm / min. The maximum load value during the peeling process is recorded. After testing 5 valid data points for each sample, the average value is taken. The results are shown in Table 1.
[0032] Flexural strength test: According to GB / T 9341-2008, the test is carried out by using a three-point bending method on an electronic universal testing machine. The copper clad laminates prepared in the examples and comparative examples are cut into standard specimens. The fulcrum spacing is set at 64 mm, the loading indenter radius is 5 mm, and the test speed is 2 mm / min. The maximum flexural stress value when the specimen breaks is recorded. The arithmetic mean of three valid measurement values is recorded as the final result. The results are shown in Table 1.
[0033] Heat resistance performance: According to GB / T 7141-2022, the copper clad laminates prepared in the examples and comparative examples are cut into standard specimens, placed in a forced ventilation aging oven, and accelerated aging is carried out at 180 °C for 1000 h. After being transferred to a desiccator and cooled to room temperature, the retention rates of thermal conductivity and peel strength are tested. The arithmetic mean of three valid measurement values is recorded as the final result. The results are shown in Table 1.
[0034] Table 1 Performance Test Results
[0035] Data Analysis: As can be seen from the data of Examples 1 - 3 in Table 1, the copper clad laminates prepared by the present invention exhibit balanced and excellent performance in terms of thermal conductivity, peel strength and flexural strength. It is speculated that its advantages stem from the synergistic effect of branched biphenyl and epoxy-functionalized aluminum nitride. The three-dimensional topological structure of branched biphenyl may form covalent bonds with the epoxy groups on the surface of aluminum nitride and the epoxy matrix through multiple active sites, constructing a continuous thermal conduction network; meanwhile, its rigid aromatic ring skeleton can enhance the molecular chain rigidity of the resin matrix, thereby improving the flexural strength.
[0036] As can be seen from the data of Example 2 and Comparative Example 1 in Table 1, Example 2 has advantages over Comparative Example 1 in terms of thermal conductivity and heat resistance retention rate. It is speculated that the difference is due to the structural difference between branched biphenyl and 1,3,5-tris(4-aminophenyl)benzene. The three-dimensional topological structure of branched biphenyl may construct a more effective thermal conduction network through multiple biphenyl units, and the spatial extensibility of the branched structure may enhance the rigidity of the resin cross-linking network, reducing the movement of molecular chain segments at high temperatures, thereby delaying the performance degradation during the thermal aging process. In addition, the π-π interaction between the biphenyl units of branched biphenyl may form auxiliary physical cross-linking points, synergistically improving the interfacial adhesion strength, which may be the key factor for the relatively high peel strength retention rate.
[0037] As can be seen from the data of Example 2 and Comparative Example 2 in Table 1, Example 2 shows better performance than Comparative Example 2 in terms of flexural strength and heat resistance, indicating that the surface modification of aluminum nitride by epoxidation is the key. The epoxy groups react with the amino groups of branched biphenyl to form chemical bonds, which may generate stronger interfacial binding force, effectively transfer stress and inhibit the propagation of microcracks. The unmodified surface of aluminum nitride lacks active groups and may only bind to the resin through physical adsorption, which is prone to interfacial slippage when stressed.
[0038] As can be seen from the data of Example 2 and Comparative Example 3 in Table 1, the performance difference between Example 2 and Comparative Example 3 shows that the branched structure has more advantages than mono-aminobiphenyl. The single amino group of 4-aminobiphenyl may only achieve single-point bonding of aluminum nitride, while branched biphenyl can form a three-dimensional network. This multidentate coordination effect may significantly enhance the filler-resin interfacial strength, and at the same time, the steric hindrance effect of the branched structure can more effectively prevent the settlement and agglomeration of fillers.
[0039] From the data of Example 2 and Comparative Example 4 in Table 1, it can be seen that there is a lack of chemical bonding between unmodified aluminum nitride and the resin matrix, which may result in obvious interfacial defects. Moreover, in the absence of branched biphenyl as a molecular bridging agent, the amino group of branched biphenyl can react with the epoxy groups of the filler and the resin, and the benzene ring can interact with the physical entanglement of the resin to jointly form a "chemical anchoring - physical interlocking" dual interfacial enhancement mechanism.
[0040] From the data of Example 2 and Comparative Example 5 in Table 1, it can be seen that Example 2 using an anhydride curing agent shows better heat resistance stability than the amine curing agent in Comparative Example 5. It is speculated that the difference is due to different curing mechanisms. Anhydride curing may form a denser crosslinked network, and the ester bond structure has better thermal stability than the ether bond structure cured by amines. The rigid cyclic structure of methyl nadic anhydride may restrict the movement of molecular segments and reduce the free volume expansion at high temperatures. In addition, the characteristic of slower anhydride curing reaction may be beneficial to the directional assembly of branched biphenyl and the filler, forming a more ordered heat conduction path. The rapid reaction of the amine curing agent may cause uneven distribution of the filler, resulting in an increase in interfacial defects and affecting the long-term heat stability.
[0041] Those of ordinary skill in the art should understand that: the discussion of any above embodiments is only exemplary and is not intended to imply that the scope of the present invention is limited to these examples; under the concept of the present invention, the technical features in the above embodiments or different embodiments can also be combined, the steps can be implemented in any order, and there are many other variations in different aspects of the present invention as described above, which are not provided in detail for the sake of brevity.
Claims
1. A high thermal conductivity and high heat resistance copper clad laminate, characterized in that, The core layer is made of a prepreg, and both sides are covered with electrolytic copper foils; the prepreg is obtained by impregnating a pretreated substrate in a resin solution and pre-curing; The pretreated substrate is obtained by subjecting a glass fiber cloth to plasma treatment; The preparation steps of the resin solution are as follows: (1) Add 1,3,5-tris(4-aminophenyl)benzene and biphenyl-4-carbonyl chloride to tetrahydrofuran, cool down to 0-5 °C, add triethylamine, stir for 5-15 min, then heat up to 30-40 °C, and stir and react for 15-25 h, and purify to obtain branched biphenyl; (2) Add aluminum nitride to an ethanol / deionized water mixture, ultrasonicate for 10-30 min, then add silane coupling agent KH-560, heat up to 50-60 °C, stir and react for 5-7 h, and purify to obtain epoxidized aluminum nitride; (3) Add epoxidized aluminum nitride and branched biphenyl to a methanol / deionized water mixture, adjust the pH to 8.1-8.6 with sodium hydroxide, heat up to 80-90 °C, reflux and stir and react for 20-28 h, and purify to obtain branched biphenyl-modified aluminum nitride; (4) Mix bisphenol A epoxy resin, methyl nadic anhydride curing agent and branched biphenyl-modified aluminum nitride, heat up to 75-85 °C and stir for 1-2 h, cool down to room temperature, then add acetone, and stir for 15-25 min to obtain the resin solution; In the step (1), the weight ratio of 1,3,5-tris(4-aminophenyl)benzene, biphenyl-4-carbonyl chloride, tetrahydrofuran and triethylamine is 3.5:8.2-9.2:15-25:3-3.5; In the step (2), the weight ratio of aluminum nitride, ethanol / deionized water mixture and silane coupling agent KH-560 is 20-30:200-300:0.2-1; In the step (3), the weight ratio of epoxidized aluminum nitride, branched biphenyl and methanol / deionized water mixture is 20-30:1.5-3.5:200-300; In the step (4), the weight ratio of bisphenol A epoxy resin, methyl nadic anhydride curing agent, branched biphenyl-modified aluminum nitride and acetone is 80-120:50-80:20-30:65-95.
2. The high thermal conductivity and high heat resistance copper clad laminate according to claim 1, characterized in that, The thickness of the electrolytic copper foil is 15-20 μm, and the roughness Rz is 2.5-3.5 μm.
3. The high thermal conductivity and high heat resistance copper clad laminate according to claim 1, characterized in that, The temperature of the pre-curing is 145-155 °C, and the time is 6-10 min.
4. The high thermal conductivity and high heat resistance copper clad laminate according to claim 1, wherein The resin content after the pretreated substrate is impregnated in the resin solution is 40%-45%.
5. The high thermal conductivity and high heat resistance copper clad laminate according to claim 1, wherein, The thickness of the glass fiber cloth is 0.4-0.6 mm.
6. The high thermal conductivity and high heat resistance copper clad laminate according to claim 1, wherein In the step (2), the volume ratio of ethanol to deionized water in the ethanol / deionized water mixture is 1:3; in the step (3), the volume ratio of methanol to deionized water in the methanol / deionized water mixture is 1:
4.
7. The high thermal conductivity and high heat resistance copper clad laminate according to claim 1, characterized in that, In the step (2), the particle size D50 of aluminum nitride is 0.5-1 μm.
8. The high thermal conductivity and high heat resistance copper clad laminate according to claim 1, wherein, In the step (4), the type of bisphenol A epoxy resin is E-51.
9. A method for preparing a high thermal conductivity and high heat resistance copper clad laminate according to any one of claims 1-8, characterized in that, It includes the following steps: S1: Take a glass fiber cloth, dry it at 110 - 130 °C for 1.5 - 2.5 h, then place it in a plasma cleaner and treat it with argon plasma. The power is 250 - 350 W and the treatment time is 3 - 8 min to obtain a pretreated substrate; S2: Immerse the pretreated substrate in a resin sizing solution and pre-cure it to obtain a prepreg; S3: Take the prepreg as the core layer, cover both sides with electrolytic copper foil, and form it using a vacuum hot press under the following conditions: The first stage: heat up to 100 - 120 °C at a rate of 2 - 4 °C / min, maintain a pressure of 4 - 6 MPa, and keep the temperature and pressure for 20 - 40 min. The second stage: continue to heat up to 170 - 190 °C at a rate of 2 - 4 °C / min, increase the pressure to 8 - 12 MPa, and keep the temperature and pressure for 70 - 110 min. The third stage: cool down to 55 - 65 °C at a rate of 0.5 - 3 °C / min and then release the pressure to obtain a laminated board; S4: Under nitrogen protection, post-cure the laminated board at 215 - 225 °C for 1.5 - 2.5 h, let it stand at room temperature for 36 - 50 h, and then cut it to obtain a high thermal conductivity and high heat resistance copper clad laminate.
Citation Information
Cited By
High-strength wear-resistant multilayer ceramic substrate and preparation method thereof
CN120554098A